2022
DOI: 10.1186/s12889-022-13087-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in digital health literacy and future anxiety between health care and other university students in England during the COVID-19 pandemic

Abstract: Background This study investigates university students’ digital health literacy and web-based information-seeking behaviours during the early stages of the COVID-19 pandemic in England. It compares undergraduate and postgraduate students in non-health related subjects with health care students, many of whom were preparing for, or working in, frontline roles. The survey was conducted as part of a wider study by the COVID-HL research consortium. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…It must be acknowledged that though previous studies have not examined the intermediary role of information accuracy, some have found a link between DHL and information accuracy. 8 , 26 Similarly, the link between information accuracy and subjective well‐being has been established. 13 , 16 It can be gleaned from these findings a possible mediating role of information accuracy, which supports the findings of this current study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It must be acknowledged that though previous studies have not examined the intermediary role of information accuracy, some have found a link between DHL and information accuracy. 8 , 26 Similarly, the link between information accuracy and subjective well‐being has been established. 13 , 16 It can be gleaned from these findings a possible mediating role of information accuracy, which supports the findings of this current study.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Extant researchers have discovered that higher DHL is associated with subjective well‐being among young adults. 19 , 26 , 27 For example, in China, a positive association between COVID‐DHL and the psychological well‐being of students has been reported. 15 , 28 Similarly, Nguyen et al 16 in Vietnam established that COVID‐DHL positively influences the subjective well‐being of students.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have examined future anxiety and the impact of health literacy, particularly among college students ( 18 , 19 ). It was found that higher health literacy was associated with lower future anxiety among Polish adults ( 18 ).…”
Section: Introductionmentioning
confidence: 99%